The Problematical (yet Valuable) Correspondence of a Hunted Heretic: The Case of the Dutch Anabaptist and Spiritualist David Joris (c. 1501–1556) - Waite, Gary K. (Renaissance and Reformation / Renaissance et Réforme, 2024)
In 1536 the Dutch Anabaptist David Joris (c. 1501–56) was proclaimed an Anabaptist messiah in the aftermath of Anabaptist Münster. When his and his followers’ apocalyptical expectations failed to materialize in late 1538, Joris fled Delft for Antwerp, then in 1544 he fled again to Basel, where he dissimulated successfully until his death. He also moved away from external fulfillment of prophecy to a fully internalized religiosity. Joris maintained contact with a widely diverse following through his missives, over 1,200 of which have survived in three printed editions from the early seventeenth century and at least one manuscript collection. This article conducts a close reading of a small sample of Joris’s late correspondence and some of his more famous missives to help explain why his letters appealed to readers, despite, or because of, their author’s intentionally obscure “spiritualistic” writing style. They offered a sense of belonging to a spiritual elite who could comprehend the meaning of creation and life. They also reveal much about Joris’s supporters as well as the significant shifts in Joris’s thinking.